(untitled) - Walker, Alice (New York, 2004)
A well-published, numerous-times-divorced woman leaves her lover to embark on a personal journey that begins on the Colorado River and traverses through her past and into her future, while her lover begins his own parallel voyage.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy